The linguistic aspect behind the changing attitudes towards 'globalisation' and 'deglobalisation' of economic processes (a case study of the German print media) - Tatyana F. Krivtsova; Valentina V. Kucheryavenko (Peoples' Friendship University of Russia (RUDN University), 2019)
The study uncovers the attitudes towards globalisation and deglobalisation by studying the language of German print media ranging between 1999 and the present time. The authors provide descriptive interpretations of the two concepts, while focusing primarily on their two underlying aspects: the expansion of corporate activities, and people's prosperity. In particular, the study looks at the linguistic aspect of the dynamics of media coverage of major company mergers and the subject of the top management's financial liability. The authors discern some of the major linguistic indicators of the attitudes towards globalisation and deglobalisation, including the use of attributives, often expressed through superlative adjectives, metaphors, allegory, and irony.